The Development of the First Nations Children Wellbeing Measure - Drawson, Alexandra S.; Toombs, Elaine; Blain, Jay; Bobinski, Tina; Dixon, John; Paavola, Natalie; Mushquash, Christopher J. (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: The overall goal of this project was to implement a measurement tool intended to assess the wellbeing of First Nations children within the Robinson Superior Treaty Area.